# How do you solve #x^2+3x+2=0#?

##### 2 Answers

#### Answer:

The solutions for the equation are:

#### Explanation:

We can solve the expression by first factorising.

Factorising by **splitting the middle term**

Equating the factors with zero:

#### Answer:

x=-2 or x=-1

#### Explanation:

Two standard ways to solve a quadratic equation:

Firstly you could factorise it to the form:-

Therefore we need two numbers that satisfy:-

So the expression is:-

It's then trivial to see that if

The other solution is to use the formula for the solution of a quadratic equation:

=>

** #a=1, b=3, c=2#** so we have:

#x=(-3+sqrt(9-8))/2=-1# or #x=(-3-sqrt(9-8))/2=-2#

The same two solutions